Ivanina T. V. Methods of formation of onomastic correspondence while translating toponyms (on the basis of English-Ukrainian dictionaries) - Ivanina T. V. (Philological Treatises, 2020)
The article deals with rendering English toponyms into Ukrainian, in particular, the principles and methods of translating the country names are considered. Special attention is paid to the recent studies of scholars in this field.